Effect of Macronutrient Feed Combinations on Bioconversion, Survival, Growth, and Nutritional Value of Hermetia illucens Larvae - Sagita, Fitria; Euis Nursaadah; Deni Parlindungan; Sutarno; Bhakti Karyadi (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Organic wastes of tilapia offal, coconut pulp, and plantain are rarely optimally utilized, but they can be degraded by BSF larvae into nutritious biomass. This study aims to analyze the combination of organic waste macronutrient feed on bioconversion, survival, growth (weight, length, and thickness), and nutritional value (protein, fat, and carbohydrates) of BSF prepupae, using the Completely Randomized Design (CRD) method, 4 treatments P1 (50% tilapia offal: 25% plantain: 25% coconut pulp), P2 (25% tilapia offal: 50% plantain: 25% coconut pulp), P3 (25% tilapia offal: 25% plantain: 50% coconut pulp), P4 (33.3% tilapia offal: 33.3% plantain: 33.3% coconut pulp) and 3 repetitions. All treatments resulted in optimal survival (100%, survival). P4 produced an ECD value of 0.034% and WRI of 0.032% indicating the best efficiency and waste reduction. P1 was the best variation for weight at 5.69 g, length 19.7 mm, and thickness 5.8 mm. The Post Hoc Tuckey test showed no significant difference between treatments in weight and thickness parameters, but not in length parameters (<0.05). The protein content of P1 43.75%, fat P2 29.764%, and carbohydrate P2 1.374% were close to SNI 7994:2014 (meat bone meal, quality II). It was concluded that macronutrient feed waste affects bioconversion, survival, growth and nutritional value of BSF.